Synergistic effect of adding bioglass and carbon nanotubes on poly (lactic acid) porous membranes for guided bone regeneration - de Moura, Nayara Koba; Martins, Eduardo Ferreira; Oliveira, Rodrigo Luiz Moraes Saldanha; de Brito Siqueira, Idália Aparecida Waltrick; Machado, João Paulo Barros; Esposito, Elisa; Amaral, Suelen Simões [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP]; Passador, Fabio Roberto; de Sousa Trichês, Eliandra (Elsevier, 2020)
Polymer membranes have been widely used in guided bone regeneration (GBR), especially when it comes to their use in dentistry. Poly (lactic acid) (PLA) have good mechanical properties such as flexibility, which allows the material to be moldable and also has biocompatibility and biodegradation. Besides that, bioglass (BG) incorporated into the polymer matrix can promote osteoinduction properties and osteoconduction properties to the polymer-ceramic biocomposite. The membranes are also required to exhibit antimicrobial activity to prevent or control the proliferation of pathogenic microorganisms, and the addition of carbon nanotubes (CNT) can assist in this property. The porous membranes of PLA with the addition of different contents of BG and CNT were obtained by solvent casting in controlled humidity method, and the synergistic effect of the addition of both fillers were investigated. The membranes showed pores (3–11 μm) on their surface. The addition of 5 wt% BG causes an increase in the surface porosity and bioactivity properties of the PLA. The agar diffusion test showed antimicrobial activity in the membranes with addition of CNT. In vitro results showed that the porous membranes were not cytotoxic and allowed cell activity and differentiation. Thus, BG collaborated to increase biological activity while CNT contributed to microbial activity, creating a synergistic effect on PLA porous membranes, being this effect more evident for PLA/5BG/1.0CNT. These results indicated a promising use of this new biomaterial for the production of porous membranes for GBR.
Keywords: Antimicrobial; Bioglass; Carbon nanotubes; GBR; Poly (lactic acid)